Analisa Identifikasi Bahaya Menggunakan Metode JSA dan HIRADC pada Pekerjaan Pembersihan Tangki (Studi Kasus : PT. Sagara Mutiara Teknik ) - Nagara, M Arga Dita; Dahda, Said Salim (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
Work accidents are one of the problems that are often encountered in the world of the construction industry. The main cause of work accidents is unsafe action. This happens because there is a lack of awareness about the magnitude of the risks that must be borne by all elements of the company. One of the high-risk jobs carried out by PT. Sagara Mutiara Teknik is tank cleaning work. In the hazard identification stage, tank cleaning work is carried out using the JSA method. Furthermore, risk assessment and control recommendations are carried out using the HIRADC method. There are several types of potential hazards found in tank cleaning work, namely falling from a height, sharp materials, slipping, dust exposure, falling materials, chemical exposure. Recommendations for improvement are made after knowing the potential hazards and implemented in the occupational safety and health management system to reduce the risk of work accidents that occur in tank cleaning work.